2016
DOI: 10.1590/1983-40632016v4642180
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizal fungi on the vegetative development of citrus rootstocks1

Abstract: The use of arbuscular mycorrhizal fungi (AMF) in the production of rootstocks is an alternative to accelerate plant growth. However, their response depends on the symbionts species and environment. This study aimed at evaluating the influence of AMF species [Scutelospora heterogama, Gigaspora margarita, Glomus etunicatum, Acaulospora sp. and a control (non-inoculated)] on the vegetative development of citrus rootstocks {citrange 'Fepagro C37 Reck' [P. trifoliata (L.) Raf. x C. sinensis (L.) Osbeck.] and 'Kumqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Nunes et al (2011) observed in their study that the Okinawa peach rootstock inoculated with AMF Glomus etunicatum (Becker & Gerd) kept in a protected environment showed larger diameter, height, leaf area, fresh and dry mass of the root and shoot than non-inoculated plants. In addition, Back et al (2016) evaluated the response of the citrange 'Fepagro C37 Reck' to inoculation with Scutellospora heterogama (TH Nicolson & Gerd. ), Gigaspora margarita (Becker & Hall), Glomus etunicatum (Becker & Gerd) and Acaulospora sp.…”
Section: Resultsmentioning
confidence: 99%
“…Nunes et al (2011) observed in their study that the Okinawa peach rootstock inoculated with AMF Glomus etunicatum (Becker & Gerd) kept in a protected environment showed larger diameter, height, leaf area, fresh and dry mass of the root and shoot than non-inoculated plants. In addition, Back et al (2016) evaluated the response of the citrange 'Fepagro C37 Reck' to inoculation with Scutellospora heterogama (TH Nicolson & Gerd. ), Gigaspora margarita (Becker & Hall), Glomus etunicatum (Becker & Gerd) and Acaulospora sp.…”
Section: Resultsmentioning
confidence: 99%
“…Inoculation with G. etunicatum favored the growth of rootstocks, considering the height and stem diameter variables, unlike G. clarum, which did not promote the growth of plants in any of the variables analyzed. Back et al (2016), working with 'Kumquateiro' [Fortunella hindsii (L.) Swingle] and 'Fepagro C37 Reck' citrange [P. trifoliate (L.) Raf. C. sinensis (L.) Osbeck.]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies show that indigenous AMF give the maximum effect [51]. Therefore, in order to ensure the success of reclamation, a series of factors need to be considered in the process of mycorrhizal microbial reclamation, such as the production and quality control of microbial agents in large-scale microbial reclamation, species compatibility with the target environment (e.g., edaphic and climatic conditions in the reclamation area), the degree of spatial competition with other soil organisms in the target niche, host plant species and cultivars, and the timing of inoculation [52,53]. Furthermore, small-scale field experiments are needed before large-scale mycorrhizal reclamation is attempted.…”
Section: Discussionmentioning
confidence: 99%